1978
DOI: 10.1073/pnas.75.10.4699
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ornithine decarboxylase activity in Escherichia coli by positive and negative effectors.

Abstract: Two effectors of ornithine decarboxylase (ODC; L-ornithine carboxy-lyase, IC 4.1.1.17) have been extracted from an ODC-(speC) mutant, Escherichia coli MA 255. One of these is an ODC inhibitor (M, 15,000 ± We reported (1, 2) that the activity of ornithine decarboxylase (ODC; L-ornithine carboxy-lyase, EC 4.1.1.17) can be inhibitied by a specific protein, the ODC antizyme, and proposed (3) that macromolecular activators of ODC may also exist to balance the inhibitory action of the ODC antizyme. The appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…This copurification of an inhibitory protein is similar to that described in purifying ornithine decarboxylase, the other putrescine biosynthetic enzyme in E. coli. An acidic protein inhibitor, termed ornithine decarboxylase antizyme, was found to copurify with ornithine decarboxylase in the initial stages of purification (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This copurification of an inhibitory protein is similar to that described in purifying ornithine decarboxylase, the other putrescine biosynthetic enzyme in E. coli. An acidic protein inhibitor, termed ornithine decarboxylase antizyme, was found to copurify with ornithine decarboxylase in the initial stages of purification (16).…”
Section: Methodsmentioning
confidence: 99%
“…Pathway I involves the decarboxylation of ornithine; pathway II involves the decarboxylation of arginine to agmatine, followed by the removal of urea from agmatine by agmatine ureohydrolase. Regulation of the biosynthetic enzymes if complex (16,20); their regulation involves both transcriptional and posttranslational mechanisms (3,13,14,25,26,29,30). Although the intracellular level of putrescine is constant as well as proportional to the growth rate (4), the relative use of the two polyamine biosynthetic pathways can vary considerably (23,26), depending on the nutritional supplements provided.…”
mentioning
confidence: 99%
“…Although inhibition of ODC by Az is reversible and active ODC can be recovered from inactive ODC-Az complexes under certain conditions (8), there is also substantial evidence involving Az in ODC degradation (9,10). In Escherichia coli, the posttranslational control of the activities of the polyamine biosynthetic enzymes ODC and arginine decarboxylase (ADC; L-arginine carboxy-lyase, EC 4.1.1.…”
mentioning
confidence: 99%
“…It is believed that the regulation of ornithine decarboxylase activity is important in the regulation of polyamine biosynthesis in Escherichia coli. Ornithine decarboxylase of E. coli is stimulated by GTP (1,6) and inhibited by ppGpp (7,19), polyamines (1,23), and antizymes (13,18). It has been reported that two basic E. coli antizyme proteins are ribosomal proteins S20/L26 and L34 (18), but other major ribosomal proteins also show antizyme activity (11).…”
mentioning
confidence: 99%